2020
DOI: 10.1021/acs.jafc.9b07238
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Potent Odorants Causing a Pickle-like Off-Odor in Moutai-Aroma Type Baijiu by Comparative Aroma Extract Dilution Analysis, Quantitative Measurements, Aroma Addition, and Omission Studies

Abstract: A potent unpleasant aroma presenting a pickle-like off-odor in Moutai-aroma type Baijiu was studied by comparative aroma extract dilution analysis (AEDA). Two Moutai-aroma type Baijiu samples, one having no off-odor (A) and the other one presenting pickle-like off-odor (B), were selected for chemical analysis and sensory evaluation. The aroma compounds were isolated by headspace solid-phase microextraction and liquid–liquid extraction. AEDA, quantitative analysis, and odor activity value calculation were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…The analysis results showed that 51 and 48 aroma-active volatiles were detected in glutinous and non-glutinous sorghum, respectively ( Table 3 ). Most of the aroma compounds detected in the cooked sorghums have also previously been identified in Chinese Baijiu [ 6 , 7 , 14 , 15 ], indicating that the aroma compounds in sorghum contribute to the overall flavor of Baijiu. The 52 different identified aroma volatiles included 14 aldehydes, 13 terpenes, 8 acids, 5 ketones, 5 alcohols, 5 heterocyclic compounds, 1 sulfur-containing and 1 aromatic compound.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis results showed that 51 and 48 aroma-active volatiles were detected in glutinous and non-glutinous sorghum, respectively ( Table 3 ). Most of the aroma compounds detected in the cooked sorghums have also previously been identified in Chinese Baijiu [ 6 , 7 , 14 , 15 ], indicating that the aroma compounds in sorghum contribute to the overall flavor of Baijiu. The 52 different identified aroma volatiles included 14 aldehydes, 13 terpenes, 8 acids, 5 ketones, 5 alcohols, 5 heterocyclic compounds, 1 sulfur-containing and 1 aromatic compound.…”
Section: Resultsmentioning
confidence: 99%
“…Volatile sulfides play a remarkable role in the aroma of food and beverages, even when present at low concentrations [ 39 , 40 ]. Recently, Wang et al found that the imbalance of sulfides will lead to the off-odor in soy sauce aroma-type Baijiu; however, these compounds might contribute to the overall aroma of Baijiu at relatively low concentrations [ 41 ]. In this study, a total of 37 sulfides ( Table 3 ) were identified, of which 28 compounds have not been reported before in Baijiu.…”
Section: Resultsmentioning
confidence: 99%
“…An automatic headspace sampling system (MultiPurpose Sample MPS 2 with a SPME adaptor, from Gerstel Inc., Muülheim, Ruhr, Germany) with a 50/30 μm divinylbenzene/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) fiber (2 cm, Supelco Inc., Bellefonte, PA, USA) was used to extract the volatile compounds. Following a method presented in the literature [ 41 ], the Baijiu sample was diluted with ultrapure water to a final concentration of 10% ethanol by volume. A total of 10 mL diluted Baijiu sample was transferred into a 20 mL screw-capped vial and saturated with 3 g of NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…The OAV was obtained from a compound concentration divided by its odor threshold [22]. Herein, the major-ity of the threshold values were taken from the literature [23][24][25]. As shown in Table 3, 42 compounds yielded an OAV ≥ 1 in both M and T samples, which indicated that these odorants may have a major contribution to the characteristic aroma.…”
Section: Confirmation Of the Key Compounds Related To The Aroma Profile Differences Between Modern And Traditional Type Xiaoqu Baijiumentioning
confidence: 99%